Publication trends on sports sociology: Global perspectives and emerging themes - Sobarna, Akhmad; Setiawan, Edi; Yudha Isnaini, Lalu Moh; Ahmedov, Farruh; Gazali, Novri; Abdullah, Khairul Hafezad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study examined the depiction of publication trends and the transformation of scholarly discourse within sports sociology publications. The investigation utilised the Scopus and WoS databases to compile a comprehensive list of sports sociology publications. Employing ScientoPy and VOSviewer, the study dynamically constructed science maps and visualisation networks. In the Scopus database, there were 516 publications, and in the WoS, 216, resulting in 732 publications, constituting 79.13% of the overall count between 1990 and 2022. Sports Sciences emerged as the predominant field with 119 publications, and the most prolific source title over the three decades was the International Review for the Sociology of Sport. The United States and Germany stood out as the top two countries, each contributing over 100 publications. The keyword “sports sociology” demonstrated close associations with “development,” “athlete,” and “physical education,” particularly evident since 2015. This study is poised to lay the groundwork for future endeavours to enrich and invigorate sports sociology research. It underscores the need for sports sociologists to delve into novel insights, including the interplay between sports sociology and mental health, gender disparities, sports injury management, and artificial intelligence. The intriguing social dimensions of physical education and sports training are underscored for their significance in shaping daily human activities, behaviours, and emotions.